THE MAJOR CHALLENGES TEACHERS FACE WHEN INTEGRATING GAMES INTO THE PROCESS OF TEACHING ENGLISH TO YOUNG (Academia Science Repository, 2023)
Teaching English to young learners using games is a promising approach to engage and motivate students. However, teachers encounter various challenges when incorporating games into their teaching practices. This article explores the major challenges faced by teachers when using games to teach English to young learners. The review identifies time-related challenges, classroom management difficulties, material and resource limitations, and instructional challenges. Potential solutions to these challenges are also discussed. The implications of the findings highlight the importance of understanding context-specific challenges and further research in this area. Overall, while games offer valuable benefits in teaching English to young learners, addressing and overcoming the challenges is essential for successful integration.